Effects of the ammonium loading rate on nitrite-oxidizing activity during nitrification at a high dose of inorganic carbon. Issue 8 (3rd July 2018) - Choi, Minkyu; Cho, Kyungjin; Jeong, Dawoon; Chung, Yun-Chul; Park, Joonhong; Lee, Seockheon; Bae, Hyokwan
ABSTRACT: In this study, the effects of the ammonium loading rate (ALR) and inorganic carbon loading rate (ILR) on the nitrification performance and composition of a nitrifying bacterial community were investigated in a moving bed biofilm reactor, using poly(vinyl alcohol) (PVA) sponge cubes as a supporting carrier. Between the two ALRs of 0.36 and 2.16 kg-N m −1 d −1, stable partial nitritation was achieved at the higher ALR. Inorganic carbon was dosed at high levels: 33.1, 22.0, 16.4, 11.0, and 5.4 times the theoretical amount. Nonetheless, nitrification efficiency was not affected by the ILR at the two ALRs. Quantitative PCR analysis of ammonia- and nitrite-oxidizing bacteria revealed that ALR is an important determinant of partial nitritation by accumulating ammonia-oxidizing bacteria in the nitrification system. In comparison, two nitrite-oxidizing bacterial genera ( Nitrobacter and Nitrospira ) showed almost the same relative abundance at various ALRs and ILRs. Terminal restriction fragment length polymorphism targeting the gene of ammonia monooxygenase subunit A revealed that Nitrosomonas europaea dominated under all conditions.